Biochemical Characterization of Oyster and Clam Galectins: Selective Recognition of Carbohydrate Ligands on Host Hemocytes and Perkinsus Parasites - Vasta, Gerardo R.; Feng, Chiguang; Tasumi, Satoshi; Abernathy, Kelsey; Bianchet, Mario A.; Wilson, Iain B. H.; Paschinger, Katharina; Wang, Lai-Xi; Iqbal, Muddasar; Ghosh, Anita; Amin, Mohammed N.; Smith, Brina; et al. (Frontiers in Chemistry, 2020)
Both vertebrates and invertebrates display effective innate immunity for defense against microbial infection, including diversified repertoires of soluble and cell-associated lectins that mediate recognition and binding interactions with potential pathogens, and can activate downstream effector pathways that clear them from the host internal milieu. Galectins are widely distributed and highly conserved lectins that have key regulatory effects on both innate and adaptive immune responses. In addition, galectins can function as recognition receptors in innate immunity, by binding exogenous (“non-self”) glycans on the surface of potentially pathogenic microbes, parasites, and fungi. Like most invertebrates, eastern oysters (Crassostrea virginica) and softshell clams (Mya arenaria) can effectively respond to most immune challenges through soluble and hemocyte-associated lectins. However, the protozoan parasite Perkinsus marinus, successfully infects and causes “Dermo” disease in the eastern oyster. The sympatric Perkinsus chesapeaki, initially isolated from infected M. arenaria clams, can also be present in oysters, and there is little evidence of pathogenicity in either clams or oysters. In this review, we discuss selected observations from our studies on the mechanisms of Perkinsus recognition that are mediated by galectin-carbohydrate interactions. We identified in the oyster two galectins that we designated CvGal1 and CvGal2, that strongly recognize P. marinus trophozoites. In the clam we also identified galectin sequences, and focused on one (that we named MaGal1) that also recognizes Perkinsus species. Here we describe the biochemical characterization of CvGal1, CvGal2, and MaGal1 with focus on the detailed study of the carbohydrate specificity, and the glycosylated moieties on the surfaces of the oyster hemocytes and the two Perkinsus species (P. marinus and P. chesapeaki). Our goal is to gain further understanding of the biochemical basis for the interactions that lead to recognition and opsonization of the Perkinsus trophozoites by the bivalve hemocytes. These basic studies on the biology of host-parasite interactions may contribute to the development of novel intervention strategies for parasitic disease on biomedical interest.